Analisis Perhitungan Quantity Take Off Struktur Jembatan Beton Bertulang Menggunakan Metode BIM (Revit) (Studi Kasus: Jembatan Ruas Batu Panjang – Pangkalan Nyirih, Kecamatan Rupat) - Nadia Sahira; Dedi Enda (Lembaga Teewan Journal Solutions, 2026)
The development of Building Information Modeling (BIM) provides an effective alternative for Quantity Take Off (QTO) calculations in reinforced concrete bridge construction. Conventional QTO methods based on two-dimensional drawings are prone to human error and require considerable time. This study analyzes the QTO results of the reinforced concrete structure of the Batu Panjang–Pangkalan Nyirih Bridge, Rupat District, using Autodesk Revit, compares them with conventional calculations, and evaluates their accuracy through percentage error and Root Mean Square Error (RMSE). A quantitative comparative approach was employed by modeling the bridge structure in Autodesk Revit and calculating gross concrete volume, reinforcement volume, and net concrete volume for the box culvert, abutment, wing wall, and loneng components. The results indicate strong agreement between the two methods, with an average percentage error of 0.028% for concrete and 1.247% for reinforcement. The RMSE values were 0.032% and 1.374%, respectively. The main differences were found in reinforcement calculations because Autodesk Revit models reinforcement details more precisely, including bar lengths and bends. These findings demonstrate that BIM-based QTO using Autodesk Revit is a reliable, accurate, and efficient alternative to conventional methods.